2022
DOI: 10.1002/gch2.202100097
|View full text |Cite
|
Sign up to set email alerts
|

Organoleptic and Physicochemical Properties of Soy‐Milk Yoghurt Enriched withMoringa OleiferaRoot Powder

Abstract: The prominent cause of stunting in Cameroon is zinc deficiency as reported by Anyangwe [3] and is known to affect 33% of children under the age of 5 years. Also anemia (caused by iron deficiency) was reported to be high (49.3%) among pregnant women, by the World Health Organisation. [4] Protein deficiency is aggravated by bland, starchy staple foods especially in the northern regions with corn and millet serving as the main staple foods. [2] These protein deficient meals present the risk of protein malnutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…explained that SMP offers lactose as a substrate for the used culture while the low levels of lactose in soy milk result in a relatively high pH value and low acidity in yoghurt (Lee et al, 1990;Yang and Lee, 2010). In addition, Ponka et al (2022) confirmed that yoghurt manufactured from cow's milk alone has a higher titratable acidity than yoghurt prepared from soy milk..…”
Section: Chemical Composition Of Yoghurtmentioning
confidence: 67%
See 2 more Smart Citations
“…explained that SMP offers lactose as a substrate for the used culture while the low levels of lactose in soy milk result in a relatively high pH value and low acidity in yoghurt (Lee et al, 1990;Yang and Lee, 2010). In addition, Ponka et al (2022) confirmed that yoghurt manufactured from cow's milk alone has a higher titratable acidity than yoghurt prepared from soy milk..…”
Section: Chemical Composition Of Yoghurtmentioning
confidence: 67%
“…The calcium content of yoghurt ranged from 111.2 to 293.8 mg /100g (Rojas et al, 1993;Buttriss, 1997;Garcia Martinez et al, 1998;Amellal-Chibane and Benamara, 2011). In addition, Ponka et al(2022) confirmed that adding SBP to yoghurt milk causes an increase in Fe content and a decrease in Ca content.…”
Section: Minerals Content Of Yoghurtmentioning
confidence: 89%
See 1 more Smart Citation
“…Qualitative analysis of plant parts indicated the presence of many important proteins and enzymes which are included in the synthesis of vitamins, iron transporters, and calcium storage proteins [187]. MO provides proteins for people of low income in consequence, and the plant has been expected to help to reduce kwashiorkor symptoms and its related consequences [188]. Te studies approved also that the plant parts could be an alternative resource of proteins used for the preparation of animal diets [189].…”
Section: Moringa Oleifera and Proteinsmentioning
confidence: 99%
“…Selenium (Se) and iodide (I) are also present in high concentrations in many parts of edible plants [229]. Its richness of minerals made it a great nutritional supportive plant of high biological value and could be used in the control, management, and treatment of micronutrient malnutrition in both humans and animals, help in bone growth and strength, and competing anemia [126,134,188,[230][231][232].…”
Section: Moringa Oleifera and Mineralsmentioning
confidence: 99%